2016
DOI: 10.1088/1674-4527/16/10/156
|View full text |Cite
|
Sign up to set email alerts
|

Physical parameters and orbital period variation of a newly discovered cataclysmic variable GSC 4560–02157

Abstract: GSC 4560-02157 is a new eclipsing cataclysmic variable with an orbital period of 0.265359 days. By using the published V − and R−band data together with our observations, we discovered that the O − C curve of GSC 4560-02157 may shows a cyclic variation with the period of 3.51 years and an amplitude of 1.40 min. If this variation is caused by a light travel-time effect via the existence of a third body, its mass can be derived as M 3 sini ′ ≈ 91.08M Jup , it should be a low-mass star. In addition, several physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…If we assume that the periodic change in the O − C curve exists, by analysis of equation ( 3) the sinusoidal term reveals a cyclic change with a semi-amplitude of 0.0054 d and a period of 49.92 yr. The periodic variations in W UMa binary stars are usually explained by two ideas: one is the Applegate mechanism (Applegate 1992) via magnetic activity cycles at one component or both, and the second idea is the light travel-time effect (Liao & Qian 2010;Han et al 2016) via the presence of a third body.…”
Section: Discussionmentioning
confidence: 99%
“…If we assume that the periodic change in the O − C curve exists, by analysis of equation ( 3) the sinusoidal term reveals a cyclic change with a semi-amplitude of 0.0054 d and a period of 49.92 yr. The periodic variations in W UMa binary stars are usually explained by two ideas: one is the Applegate mechanism (Applegate 1992) via magnetic activity cycles at one component or both, and the second idea is the light travel-time effect (Liao & Qian 2010;Han et al 2016) via the presence of a third body.…”
Section: Discussionmentioning
confidence: 99%
“…Sinusoidal O-C modulations have been identified or proposed in a number of additional AWD systems (e.g. Bond & Freeth 1988;Dai et al 2010;Han et al 2016), but the orbital cycles of these systems are generally either poorly sampled or have not been observed in their entirety. Previous studies have shown that these modulations cannot always be explained by the orbit of a third body (e.g.…”
Section: Third Body In the Z Cha Systemmentioning
confidence: 99%
“…The most common method for determining the period variations is to analyze the observed-calculated (O − C) diagram. We have used this method several times in the past few years to study a few eclipsing CVs such as Z Cha (Dai et al 2009), OY Car (Han et al 2015), V2051 Oph (Qian et al 2015) and GSC 4560-02157 (Han et al 2016). In this paper, we present new CCD photometric observations of AY Psc and update the orbital ephemeris.…”
mentioning
confidence: 99%